Spatial characteristics of merging decision making and implementation at highway work zone - Li, Li; Zhang, Dong (2017 4th International Conference on Transportation Information and Safety (ICTIS), 2017)
Due to special driving circumstance at work zone, driver's merging behavior differs from that at other highway segments. This study conducts a comprehensive analysis of the spatial characteristics of merging decision and implementation at the work zone. Three issues are concerned: the desired merging positions, the mechanism of merging decision-making and the successful merging position. Linear regression and logistic regression are applied to analyze the traffic flow data collected at seven upstream cross-sections of the work zone. Driver's desired merging position at upstream is found to subject to the normal distribution with an average of 283m away from the work zone taper. The problem of vehicle speeding is serious in the free flow condition, which could be owing to the improper deployment of speed limit sign. Driver's merging decision could be affected by surrounding vehicle status and its own position. The probability of merging vehicle being observed increases with the extending merging gap, faster potential leader, slower potential follower, or approaching to the work zone taper. Finally, driver's successful merging position subjects to the normal distribution with an average of 157m away from the work zone taper. Decrease of traffic density on the merging target lane could result in the successful merging positions being closer to work zone. At some speed ranges of target lane traffic, the driver needs a longer distance to accomplish merging than the condition at other speed ranges.